Point-of-Care (POC) Urinary L-Type Fatty Acid-Binding Protein (u-LFABP) Use in Critically Ill, Very Preterm Neonates - Puspitasari, Henny Adriani (Hindawi Limited, 2022)
Preterm neonates are born with fewer functional nephrons, rendering them vulnerable to secondary insult. These insults are associated with acute kidney injury (AKI); thus, structural damage must be detected as early as possible. Urinary L-type fatty acid-binding protein (u-LFABP) has been proposed as a highly suitable kidney injury biomarker during prematurity. We aimed to analyze the use of POC u-LFABP in critically ill, very preterm neonates. This study was conducted at the neonatal intensive care unit (NICU), Dr. Cipto Mangunkusumo General Hospital, from November to December 2020. Baseline characteristics were recorded from electronic medical records. u-LFABP examination utilized stored urine samples from a previous study and was performed using a LFABP POC test kit. The proportion of abnormal u-LFABP (83.3) was highest at 72 hours. Neonates with older gestational age (0-48 hours; p=0.017) and higher birth weight (0-48 hours; p=0.022, 72 hours; p=0.013) had normal u-LFABP levels. Neonates exposed to nephrotoxic agents showed higher proportion of abnormal u-LFABP (0-48 hours; p=0.006). Longer invasive mechanical ventilation (IMV) period was observed in neonates with abnormal u-LFABP levels at 0-48 hours (7.44 ± 7.9 vs. 1.50 ± 2.9 days; p=0.011). We found an association between complication rates and poorer disease outcome trends with abnormal u-LFABP; however, this relationship was not supported statistically. In conclusion, this study demonstrated that u-LFABP can be detected using bedside POC kit in critically ill very preterm neonates and those exposed to nephrotoxic agents may be at risk for kidney injury, confirmed by abnormal u-LFABP levels. © 2022 Henny Adriani Puspitasari et al.